KNOWLEDGE, ATTITUDES, PRACTICES, AND SOME RELATED FACTORS REGARDING TUBERCULOSIS PREVENTION AMONG PATIENT'S FAMILY (Vietnam Journal of Community Medicine, 2026)
Objectives: Assessing the current state of knowledge, attitudes, and practices regarding tuberculosis prevention among family members of patients and some related factors in several communes/wards of Phu Tho province in 2026.Research method: Analytical cross-sectional descriptive studyResults: The results showed that the percentage of family members of tuberculosis patients with general knowledge, attitudes, and practices regarding tuberculosis prevention was 80.2%, 77.9%, and 54.1%, respectively. Of these, correct knowledge about the causes of tuberculosis was the highest (78.6%), while knowledge of predisposing factors was the lowest (70.0%). Regarding attitudes, the highest percentage was being a positive willingness to seek treatment (71.3%), while the lowest was being willingness to advise suspected tuberculosis patients to get tested (50.9%). Correct practices regarding regular health check-ups were the highest (80.2%), while the lowest was consistently wearing masks when in contact with tuberculosis patients (24.4%). The results of the multivariate regression analysis showed that several factors were identified as being related to knowledge: primary caregiver and group advised by health workers with OR(95% CI) of 4.33(1.9-9.53), 5.83(2.75-12.34), respectively; Factors related to attitude were: primary caregiver and receiving information about tuberculosis with OR(95% CI) of 2.68(1.34-5.36), 3.3(1.55-7.2), respectively; Factors related to tuberculosis prevention practices were: primary caregiver, group advised by health workers, receiving information about tuberculosis, duration of illness with OR(95% CI) of 6.7(2.9-15.1), 2.8(1.2-6.4), 3.8(1.7-8.5), 0.4(0.2-0.9), respectively; Occupational factors such as workers and businesspeople had higher practical skills than the farmer group with OR(95% CI) of 3.2(1.0-10.1) and 12.0(3.4-42.7), respectively; these analysis results were statistically significant p
Keywords: Knowledge, attitudes, and practices regarding tuberculosis prevention, communes/wards in Phu Tho province